PLAY AND LEARN WITH TRADITIONAL LOCAL WISDOM GAMES IN PAUD INSTITUTIONS - Nurul Anam; Saiyenah; Naily Inayatul Maghfirah (FORPIM PTKIS ZONA TAPAL KUDA, 2022)
ABSTRACTIn Indonesia, the number of online game addicted in children was experienting a very dangerous development. One doctor predicted that the highers number of online game addicted was Asia. This is very ironic. Since the first, the Indonesian nation has had many traditional games that can be used in learning activities. In the midst of the dangers of online games, the RA Nurul Ulum in Sumbersalak Village used traditional local wisdom game methods and media in every learning activity. This was done so that the students continue to love and preserve the educational games of traditional local wisdom. From this background, this study aims at describing the application of traditional games in RA Nurul Ulum. The research method used was a descriptive qualitative approach. The results of the research show that the traditional local wisdom games used are engklek and jumping rope games. The application of this game can improve gross motoric skills in early childhood, stimulated children in developing cooperation, make children more creative, active, adept at jumping, jumping and being responsible in a game. From the application of this traditional game, children's gross motoric skills developed more rapidly and children get to know traditional games and their types.Keywords: Play, Learn, Traditional Local Wisdom Games, PAUD